Aplikasi Pencarian Layanan Kesehatan Berbasis Android - Irawan, Reza Yudi; Wulandari, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Health services are services provided to the community related to health, both preventive (disease prevention), promotive (improving health), curative (disease treatment), and rehabilitative (recovery) carried out by the government, local government and / or community. These health services are provided by the government, local governments, and the private sector. However, there are still many people who do not know the information on the place or location of these health services. Therefore, an android-based application is needed to improve services to the community. The purpose of this study is to produce health service applications by utilizing Location Based Service and Global Positioning Service so as to help the public to find health service information and assist in finding the location of health services because it is accompanied by the closest route to the location. Location Based Service (LBS) uses the values of the longitude and latitude points on the earth to determine the location to be inputted.